Risk factors for infection by extended-spectrum beta-lactamase producing Klebsiella pneumoniae in a tertiary hospital in Salvador, Brazil - Silva,Nanci (2006)
Nosocomial infection caused by extended-spectrum beta-lactamase producing Klebsiella pneumoniae (ESBL-Kp) have been frequently reported worldwide. We have no information on such problems in Bahia, Brazil. OBJECTIVES: Evaluate the risk factors for nosocomial infections caused by ESBL-Kp, in a tertiary hospital, in Bahia, Brazil. MATERIAL AND METHODS: We evaluated all reported cases of nosocomial infections caused by ESBL-Kp in a private, tertiary hospital, in Salvador, Brazil, from 2000 through 2004. We compared patients with a diagnosis of ESBL-Kp (cases) and patients infected by non-ESBL producing K. pneumoniae (controls). Mean age, underlying disease, and frequency of invasive procedures were compared between the two groups. History of previous use of antibiotics was also analyzed. RESULTS: Based on multivariate analysis, previous use of antibiotics, diagnosis of malignant diseases, and diabetes mellitus were independent risk factors for acquisition of ESBL-Kp infection. No correlation was found for age, use of corticosteroids, diagnosis of chronic renal failure or AIDS, and infection by ESBL-Kp. CONCLUSION: Our findings suggest that the use of antibiotics or underlying disease that increases the chance of antibiotic are the main risk factors for ESBL-Kp infections. Programs focusing on rational use of antibiotics are mandatory for prevention and control of such infections.